Second Harmonic Generation microscopy reveals collagen fibres are more organised in the cervix of postmenopausal women - Brenda F. Narice; Nicola H. Green; Sheila MacNeil; Dilly Anumba (BMC, 2016)
Abstract Background During labour, the cervix undergoes a series of changes to allow the passage of the fetoplacental unit. While this visible transformation is well-described, the underlying and causative microscopic changes, in which collagen plays a major role, are poorly understood and difficult to visualise. Recent studies in mice and humans have shown that Second Harmonic Generation (SHG) microscopy, a non-destructive imaging technique, can detect changes in the cervical collagen. However, the question of whether SHG can identify changes in the arrangement of cervical collagen at different physiological stages still needs addressing. Therefore, this study aimed to compare the cervical collagen alignment between pre- and postmenopausal women using SHG and to generate proof-of-concept data prior to assessing this technique in pregnancy. Methods Cervical biopsies from premenopausal (n = 4) and postmenopausal (n = 4) multiparous women undergoing hysterectomy for benign conditions were cross-sectionally scanned using an upright confocal microscope. SHG images were collected in Z-stacks and qualitatively evaluated using semi-quantitative scoring (0-3 in ascending degree of alignment) by assessors who were unaware of the classification of the SHG images, and quantitatively, using 2D Fourier transformation analysis. The dominant orientation and difference in dispersion of collagen fibres in each z-stack (X ± SD) was calculated and compared between groups. Results Qualitatively, collagen fibres appeared more organised in postmenopausal women, [premenopausal: median 0, range (0-1), postmenopausal: median 1.25, range (1-3); X 2 (df = 5) = 19.35, p = 0.002]. Quantitatively, there was a statistically significant difference in collagen fibre dispersion between premenopausal (5.39° ± 12.68°) and postmenopausal women (−1.58° ± 8.24°), [Welch's t-test (245.54) = 5.54, p < 0.01], with no significant differences in dispersion within each group [premenopausal, Welch's F (7, 57.23) = 1.84, p = 0.098; postmenopausal, Welch's F (7, 57.28) = 1.39, p = 0.23]. Conclusion These results suggest an increased alignment of cervical collagen in postmenopausal women which may result in increased stiffness and reduced compliance, confirm that SHG microscopy can provide qualitative and quantitative information about cervical collagen orientation without sample preparation, and support further research to explore SHG as a means of assessing cervical remodelling to predict the timing of term and preterm labour.